Association of Risperidone With Gastric Cancer: Triangulation Method From Cell Study, Animal Study, and Cohort Study - Chen, Vincent Chin-Hung; Hsu, Tsai-Ching; Lin, Chiao-Fan; Huang, Jing-Yu; Chen, Yi-Lung; Tzang, Bor-Show; McIntyre, Roger S. (Frontiers in Pharmacology, 2022)
Purpose: To examine the effects of risperidone, an atypical antipsychotic agent, on gastric cancer. Methods: A triangulation method comprising bench studies, including cell and animal experiments, and a retrospective cohort study, was subsequently performed. Results: The bench study indicated that risperidone exerted more prominent tumor inhibition effects than other atypical antipsychotics on the proliferation of KATO-III cells, a human gastric cancer cell line. Significant and dose-dependent cell viability was observed in Hs27 cells (control cells) in the presence of risperidone compared with in KATO-III cells. Both in vivo and in vitro results indicated that risperidone significantly inhibited the proliferation of KATO-III cells by inducing ROS and apoptosis, and that it suppressed the growth of xenografted KATO-III tumors in nude mice. In addition, the population-based cohort study found that risperidone users had reduced risks of gastric cancer compared with non-users, with lowered adjusted hazard ratios (HRs) for two induction periods (HR = 0.75; 95% confidence interval [CI] 0.68-0.83 for the one-year induction period, and HR = 0.68; 95% CI 0.61-0.75 for the two-year induction period). Conclusion: The findings are consistent with anticancer effects associated with risperidone, but further research and evaluations are warranted.